Delovno pravo v dobi informacijske tehnologije - Tičar, Luka (Podjetje in delo, 2016)
The paper draws attention to the labour law issues arising from the certain newly emerging forms of work, resulting from the fast development of information technology and digitalisation. In this light, the author attempts to define the notion of crowdwork and point at the legal consequences thereof for the traditional concept of labour law. The paper also highlights the fact that digitalisation of work does not have only negative consequences, yet is frequently a subject of diverse professional estimations. The author also draws attention to the general impact of digitalisation on the position of workers.
Keywords: delovno pravo; elektronsko poslovanje; informacijska tehnologija; zasebnost